Design of synchronous serial communication to control pitches of angklung - Anas Muzamil, Hamiddin (2013)
This thesis describes the control device angklung (traditional musical instrument) with a 3 octave by using microcontroller. Each angklung pitch should be shaken to produce intonation. The electric motor is used as a vibrator mechanism and installed on every pitch angklung. Parameters such as the time duration and the motor speed to needs to be controlled and this require a Motor Drivers. Angklung pitch usually arranged in a Diatonic Scale. In a frame of angklung, there is 7 pitch intonation compiled in one octave, then there are 21 motors needs to be controlled by a microcontroller to control the angklung that has 3 different octaves. If each motor requires 12 volt and 100 mA to move, then 2.1 A is required for all motor to operate simultaneously without problems. This requires Power Supply which provide 12 volt and 3 A. By using the Serial Parallel Interface (SPI), 21 connections from microcontroller to control each motor can be reduced. Because all motor drivers connected in serial connection, then the latency in motor drivers should be measure. Latency is the amount of time it takes for a system after the system receives the signal till the system is producing other signal out. If the motor drivers produce high latency, the delay produced by the angklung can be heard. The normal human ear can notice latency more than 3 ms.